Diatom biostratigraphy and age of the Pliocene Sorsdal Formation, Vestfold Hills, East Antarctica - Harwood, DM; McMinn, A; Quilty, PG (Cambridge University Press, 2000)
Fossil marine diatom assemblages from the Srsdal Formation, a deposit of diatomaceous sand from Marine Plain in the Vestfold Hills, provide age and palaeoenvironmental information from a Pliocene coastal setting in East Antarctica. Benthic and meroplanktic diatom taxa suggest deposition in a shallow coastal embayment with water depths of 20-25 m. Diatom biostratigraphy indicates that the Srsdal Formation belongs to the Fragilariopsis barronii Zone (4.5 to 4.1 Ma), through correlation to reference sections in the Ross Sea and Southern Ocean. Features of the other biota suggest higher sea-surface temperatures and reduced sea-ice cover, consistent with global records of higher sea level.